NOX4 downregulation leads to senescence of human vascular smooth muscle cells - Przybylska, Dorota (Oncotarget, 2016)
Senescence is a stress response characterized by an irreversible growth arrest and alterations in certain cell functions. It is believed that both double-strand DNA breaks (DSB) and increased ROS level are the main culprit of senescence. Excessive ROS production is also particularly important in the development of a number of cardiovascular disorders. In this context the involvement of professional ROS-producing enzymes, NADPH oxidases (NOX), was postulated. In contrary to the common knowledge, we have shown that not only increased ROS production but also diminished ROS level could be involved in the induction of senescence. Accordingly, our studies revealed that stress-induced premature senescence (SIPS) of vascular smooth muscle cells (VSMCs) induced by doxorubicin or H(2)O(2), correlates with increased level of DSB and ROS. On the other hand, both SIPS and replicative senescence were accompanied by diminished expression of NOX4. Moreover, inhibition of NOX activity or decrease of NOX4 expression led to permanent growth arrest of VSMCs and secretion of interleukins and VEGF. Interestingly, cells undergoing senescence due to NOX4 depletion neither acquired DSB nor activated DNA damage response. Instead, transient induction of the p27, upregulation of HIF-1alpha, decreased expression of cyclin D1 and hypophosphorylated Rb was observed. Our results showed that lowering the level of ROS-producing enzyme - NOX4 oxidase below physiological level leads to cellular senescence of VSMCs which is correlated with secretion of pro-inflammatory cytokines. Thus the use of specific NOX4 inhibitors for pharmacotherapy of vascular diseases should be carefully considered.